Respuesta :

[tex]1. \: (x - y) {2} \\ = {x}^{2} - 2xy + {y}^{2} \\ 2. \: (a + b) ^{2} \\ = {a}^{2} + 2ab + {b}^{2} \\ 3. \: (2x + 3y) ^{2} \\ = {(2x)}^{2} + 2.2x.3y + (3y) ^{2} \\ = {4x}^{2} + 12xy + {9y}^{2} \\ 4.(3x - 2y) ^{2} \\ = (3x) ^{2} - 2.3x.2y + (2y) ^{2} \\ = {9x}^{2} - 12xy + {4y}^{2} \\ hope \: it \: helps \\ good \: luck \: on \: your \: assignment[/tex]

Answer:

a) x^2−2xy+y^2

b) a^2 -ab+b^2

c)4x^2+12xy+9y^2

d)9x^2 -12xy+4y^2

Step-by-step explanation:

a) x^2−2xy+y^2

b) a^2 -ab+b^2

c)4x^2+12xy+9y^2

d)9x^2 -12xy+4y^2

We rewrite (x-y)^2 as (x-y) (x-y) to show and always see + sign at start for question a ) and question b)

a) x*x+x(−y)−yx−y(−y) = x^2−2xy+y^2

b) a^2 becomes a^2 -ab as a^2 -ab+b^2

c) As shown in notes attached and this will help you most.

d) the reasons we keep +4y is because -2y becomes -2y-2y and creates a plus.

Ver imagen bamboola1
ACCESS MORE